Ozawkie, Jefferson County - Milleret, Pamela (Kansas State University, The Chapman Center for Rural Studies, 2011)
Originally named "Osawkee" it is believed that this Indian Village was named in honor of the Chief of the Sak (Sauk) tribe. Perhaps, you have been told that the name means, "People of the Yellow Earth", where "Wa-sae', meaning yellow, plus 'ah-Kee meaning earth". However, contradicting statements argue that the name actually means, "People of the Outlet", in reference of the Sauk Tribe's Saginaw Bay, Michigan origin.
Pamela Milleret, “Ozawkie, Jefferson County,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/65.
Keywords: Jefferson County; Osawkee; Perry Dam; Sauk; George and William Dyer; Delaware Indians